2018
DOI: 10.1038/s41598-018-30054-z
|View full text |Cite
|
Sign up to set email alerts
|

PLVAP and GKN3 Are Two Critical Host Cell Receptors Which Facilitate Japanese Encephalitis Virus Entry Into Neurons

Abstract: Japanese Encephalitis Virus (JEV), a globally important pathogen, belongs to the family Flaviviridae, is transmitted between vertebrate hosts by mosquitoes, principally by Culex tritaeniorhynchus. The E-glycoprotein of the virus mediates its attachment to the host cell receptors. In this study, we cloned and purified JEV E-glycoprotein in pET28a vector using E. coli BL21 (DE3) cells. A pull down assay was performed using plasma membrane fraction of BALB/c mouse brain and E-glycoprotein as a bait protein. 2-Dim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 40 publications
(26 citation statements)
references
References 39 publications
0
26
0
Order By: Relevance
“…GKN3 is a gastrokine that is expressed specifically in the stomach, but its function is obscure. GKN3 expression has been found to be upregulated in gastric antral tumorigenesis and Japanese encephalitis virus‐infected brain tissues. It was reported that GKN2 forms heterodimers with TFF1 in stomach mucosal cells and regulates the extracellular function of TFFs.…”
Section: Discussionmentioning
confidence: 99%
“…GKN3 is a gastrokine that is expressed specifically in the stomach, but its function is obscure. GKN3 expression has been found to be upregulated in gastric antral tumorigenesis and Japanese encephalitis virus‐infected brain tissues. It was reported that GKN2 forms heterodimers with TFF1 in stomach mucosal cells and regulates the extracellular function of TFFs.…”
Section: Discussionmentioning
confidence: 99%
“…Mouse cortical neurons were cultured as per previously-mentioned protocol (34). Briefly, 2-day old BALB/c mouse pups’ brain cortex was isolated in calcium and magnesium-free tyrode solution, under a dissecting microscope and sterile conditions.…”
Section: Methodsmentioning
confidence: 99%
“…Usually, encephalitis is the most severe clinical appearance of JEV infection with a variety of first symptoms, including seizures, as well as acute sensory and neuromuscular functional deficiencies [119]. JEV infection of microglia [113,120], astrocytes [121] and neurons [122,123,124,125] with corresponding cellular response and possible apoptosis, as well as subsequent inflammatory response results in neuronal cell death. In addition, oedema and vascular damage may enhance damage to the tissue and cells.…”
Section: Jev Crossing the Blood–brain Barrier And Brain Infectionmentioning
confidence: 99%